New calibration data for the Fe-Ti oxide thermo-oxybarometers from experiments in the Fe-Ti-O system at 1 bar, 1,000-1,300°C and a large range of oxygen fugacities - Lattard, Dominique; Sauerzapf, Ursula; Käsemann, Martin (Contributions to mineralogy and petrology, 2005)
The current formulations of the Fe-Ti oxide thermobarometer (titanomagnetite-ilmenitess) fail to reproduce experimental results, in particular at the high temperatures that are relevant for basaltic assemblages. With the aim of improving the experimental basis of the calibration in the Fe-Ti-O system, we have synthesised assemblages of titanomagnetite-ilmenitess (Tmt-Ilmss), ilmenitess-pseudobrookitess (Ilmss-Psbss) and single-phase samples under a wide range of fO2 (fixed with CO/CO2 mixtures or by solid oxygen buffers) in sub-solidus conditions (1,000-1,300°C) at 1 bar. Runs lasted ≥24 h at 1,300°C and up to 240 h at 1,000°C and were terminated by quenching in water. All run products are polycrystalline, roughly equigranular aggregates, with grain sizes of 10-50 μm. They were examined and analysed with the SEM and EMP. Tmt compositions are broadly in accordance with the current models at moderate fO2, but significantly richer in Ti at low fO2 and high T, due to cationic vacancies. Ilmss compositions depart from the predicted values practically at all fO2 and T conditions, which is related to unsatisfactory thermodynamic models for the rhombohedral oxide. For Ilmss-Psbss assemblages the best agreement between our data and current calculations is at 1,000°C and moderately high fO2. Otherwise, experimental and calculated data strongly disagree. The experimental data set on the three Fe-Ti oxide solid solutions presented here is intended to support new versions of both the titanomagnetite-ilmenitess thermo-oxybarometer and the ilmenitess-pseudobrookitess oxybarometer.
Gesehen am 06.10.2020